Abnormal push-pull benzo[4, 5]imidazo[1, 2-a][1, 2, 3]triazolo[4, 5-e]pyrimidine fluorophores in planarized intramolecular charge transfer (PLICT) state: Synthesis, photophysical studies and theoretical calculations. (August 2022) - Taniya, Olga S.; Fedotov, Victor V.; Novikov, Alexander S.; Sadieva, Leila K.; Krinochkin, Alexey P.; Kovalev, Igor S.; Kopchuk, Dmitry S.; Zyryanov, Grigory V.; Liu, Yuanli; Ulomsky, Evgeny N.; Rusinov, Vladimir L.; Charushin, Valery N.
Abstract: The combination of excellent luminescence with high solvent polarity effect and aggregation induced emission (AIE) is an ideal combination for creating fluorophores/probes with high microenvironmental sensitivity. However, many push-pull chromophores of the D−A type in common intramolecular charge transfer (ICT) state with a significant solvatochromic effect and AIE activity, have poor luminescent properties. Herein, to overcome this problem by using reactions of nucleophilic aromatic hydrogen substitution (SN H ), we have designed a series of novel 4-heteroaryl-substituted 2-aryl-2 H -benzo[4, 5]imidazo[1, 2- a ][1, 2, 3]triazolo[4, 5- e ]pyrimidine fluorophores possessing a planarized intramolecular charge transfer (PLICT) state. All these fluorophores exhibited high luminescence quantum yields (up to 60%) and large Stokes shift values of up to 7459 cm −1 . Among them, the fluorophore 4h was found to exhibit the most pronounced positive solvatochromic effect and the probe 4f exhibited the most pronounced aggregation induced emission characteristics. This AIE behavior was further confirmed by means of time-resolved fluorescence lifetime measurements as well as DFT-assisted geometry optimization studies. In the presence of trifluoroacetic acid (TFA) compound 4h exhibited a well-pronounced acidochromism via visible color change from yellow-green to orange which returned to the original yellow-green solution after the addition of triethylamine (TEA). The Stern-Volmer constant for the probe 4h towards TFA was 38 M −1 . Finally, for the compounds 4f, g, h theoretical calculations in the ground and excited states in different solvents were carried out to confirm the PLICT process. Based on all above the herein reported PLICT fluorophores 4a-h can be successfully applied as biological probes and optical switches. Graphical abstract: Image 1 Highlights: A series of novel azoloazine fluorophores were synthesized via the reaction of nucleophilic substitution of hydrogen (SN H ). High photoluminescence quantum yields were detected both in solution and PVA films. Positive solvatochromic effect was mathematical evaluated. AIE behavior was further confirmed by time-resolved fluorescence lifetime measurements and theoretical calculations. Reversible solution state acidochromism observed with TFA. PLICT process was confirmed via geometry optimization procedure.